2000
DOI: 10.1046/j.1469-8137.2000.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus availability limit N2 fixation in bean

Abstract: Availability of nitrogen (N) and phosphorus (P) might significantly affect N # fixation in legumes. The interaction of N and P was studied in common bean (Phaseolus vulgaris), considering their effects on nodulation and N # fixation, nitrate reductase activity, and the composition of N compounds in xylem sap. The effect of N on the uptake of P by plants was estimated by analysing rhizospheric pH and P concentration in xylem sap and in plant shoots. Inoculated bean plants were grown in pots containing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 41 publications
7
48
0
1
Order By: Relevance
“…Even control plants showed a strong nodulation (Figure 1b), which reinforces the argument that the common bean is a promiscuous host regarding native soil rhizobia (Hungria et al, 2003). The addition of mineral N strongly reduced nodulation at both soil P levels (Figure 1b) since the Phaseolus-Rhizobium symbiosis is quite sensitive to soil nitrate (Westermann et al, 1981;Leidi & Rodríguez-Navarro, 2000). However, at the highest soil P level nodulation was less affected by the mineral N applied.…”
Section: Plant Growthsupporting
confidence: 77%
See 3 more Smart Citations
“…Even control plants showed a strong nodulation (Figure 1b), which reinforces the argument that the common bean is a promiscuous host regarding native soil rhizobia (Hungria et al, 2003). The addition of mineral N strongly reduced nodulation at both soil P levels (Figure 1b) since the Phaseolus-Rhizobium symbiosis is quite sensitive to soil nitrate (Westermann et al, 1981;Leidi & Rodríguez-Navarro, 2000). However, at the highest soil P level nodulation was less affected by the mineral N applied.…”
Section: Plant Growthsupporting
confidence: 77%
“…Indeed, at the highest soil P level plants under mineral N had fewer but larger nodules, with an individual nodule mass of 2.79 mg/ nodule, as compared to 2.32 and 2.07 mg/nodule in the control and inoculated plants, respectively, averaged across seed treatments. Leidi & Rodríguez-Navarro (2000) observed that the increased P supplies improved nodulation of bean plants at low N concentrations in nutrient solutions, whereas the effect of P in high N concentrations was negligible.…”
Section: Plant Growthmentioning
confidence: 94%
See 2 more Smart Citations
“…The influence of P i on symbiotic dinitrogen (N 2 ) fixation in leguminous plants has received considerable attention (Israel, 1987) but its role in maintaining nodule metabolism remains unclear. It has been observed that soybeans grown with fertilizer nitrogen (N) have a lower phosphorus (P) requirement than when N is obtained from symbiosis (Leidi & Rodríguez-Navarro, 2000). Additionally, it was demonstrated that nodules can take up P from the host, but do not readily release its P reserves to the host root (Al-Niemi et al ., 1998) suggesting that nodules form strong sinks for P. Furthermore, this important role of P in nodules is supported by the threefold higher P concentrations compared with other tissues (Vadez et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%